2020
DOI: 10.1563/aaid-joi-d-19-00273
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Analysis of Sodium Hypochlorite Decontamination for the Reuse of Implant Healing Abutments

Abstract: The re-use of healing abutments (HAs) has become common practice in implant dentistry for economic concerns and the aim of this in-vitro study was to assess the effect of sodium hypochlorite (NaOCl) in decontamination of HAs. 122 HAs (Used and sterilized n=107; New n=15) were procured from 3 centers, of which 3 samples were discarded due to perforation in sterilization pouch.  For sterility assessment, the used HAs (n=80) were cultured in Brain Heart Infusion Broth (BHI) and Potato Dextrose Agar (PDA), bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Although only 30% of the tested HAs in a study showed bacterial presence, the remaining HAs had a strong adherence of biomass (Barreiros et al 2021). Similarly, another study showed presence of no bacterial or fungal contamination on treatment with NaOCl followed by steam autoclaving, but debris was observed in scanning electron microscopy images in some regions of the thread regions primarily attributed to ledge design (Almehmadi 2021).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Although only 30% of the tested HAs in a study showed bacterial presence, the remaining HAs had a strong adherence of biomass (Barreiros et al 2021). Similarly, another study showed presence of no bacterial or fungal contamination on treatment with NaOCl followed by steam autoclaving, but debris was observed in scanning electron microscopy images in some regions of the thread regions primarily attributed to ledge design (Almehmadi 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Out of 812 articles, after elimination of articles by title/abstract, 20 articles were selected for full-text reading. Fourteen articles were provisionally selected, of which 8 articles fulfilled the inclusion criteria (Wadhwani et al 2016; Wheelis et al 2018; Chew et al 2018; Stacchi et al 2018; Sánchez-Garcés et al 2019; Jain et al 2020; Almehmadi 2021; Narvekar et al 2020), and 6 were excluded (Vezeau et al 2000; Browne et al 2012; Cakan et al 2015; Kyaw et al 2020; Barreiros et al 2021; Jain et al 2021). The PRISMA flowchart depicting the search strategy and characteristics of included and excluded articles is described in Figure 1 and Table 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The files were removed from the bags, washed in deionized water, and air-dried. We observed the files using an oblique light, and the camera (Cannon t31 Rebel) zoomed in on the flutes and cutting surfaces (Figure 1 ) [ 23 , 24 ]. The photographs were uploaded to a computer with 40× magnification and an accelerating voltage set at 15 kV.…”
Section: Methodsmentioning
confidence: 99%